White paper on Biogas Upgrading Economics – Comparison between biogas upgrading and electricity co-generation: Greece - Tritopoulou, Efthymia; Machado, Jose Vale (Technical Annals, 2024)
The present study intents to compare the existent Biogas usage options, currently used in Greece for electricity generation using co-generation engines (COGEN), and comparing it to the current trends in biogas purification, either from Anaerobic Digestion (AD) or from Landfill (LF) , for production of Biomethane, for Natural Gas (NG) grid injection or Compressed Natural Gas (CNG) for fleet fueling. The study also presents the current feed-in tariffs in place for electricity production in Greece, as a function of feedstock used to produce biogas. Study shows a better overall energy recovery from all biogas upgrading solutions – from AD and LF – than the equivalent co-generation options, by at least 2-fold. Economic yield comparison is highly dependent on the “feed-in” tariff that may be in place at each given time. In addition to land-usage of Biomethane, and analysis of possible impact in the usage of Liquefied Biomethane (Bio-LNG) in the shipping industry, given the impact of the latter in Greek economic activity.